Influence of U.V light on the thermal properties of HDPE/Carbon black composites - Sahu, Alok K.; Sudhakar, K.; Sarviya, R. M. (Elsevier, 2019)
Solar Energy is one of the most abundant renewable sources of energy and free on planet earth. For water mounted solar photovoltaic systems, HDPE material is found to be best suited for the manufacturing of floating bed structure. The major limitation in this regard is the effect of UV radiations present in the natural environment that leads to the degradation of plastic materials. In the present study, the carbon black is used as a UV resistant additive which is mixed with the base HDPE material under different concentration starting from 1% to 3%. The thermal behavior of the HDPE/Carbon black composite floats so formed are observed before and after U.V exposure. FTIR and DSC curve confirms that carbon black is dispersed uniformly in the HDPE matrix and there is no degradation in the polymer after exposure to U.V light.